Ships' logbooks from the Arctic in the pre‐instrumental period. (18th September 2015) - Ayre, Matthew; Nicholls, John; Ward, Catharine; Wheeler, Dennis
Abstract : Ships' logbooks are now an accepted part of the repertoire of data sources in climate change studies. This article examines some of the particular issues surrounding logbooks from the Arctic region in the so‐called pre‐instrumental period. Attention is given to the means by which narrative descriptions of wind, weather and sea ice cover can be reliably expressed in index form. Consideration is also given to the various means by which these data can be most effectively managed for scientific analysis as in most cases they were not recorded for such purposes. Many such logbooks remain yet to be digitized and the methods described here can be applied with equal confidence in future through such undertakings using English language documents.